Exploiting cell cycle inhibitor genes of the KRP family to control root‐knot nematode induced feeding sites in plants. (1st March 2017) - Coelho, Roberta Ramos; Vieira, Paulo; Antonino de Souza Júnior, José Dijair; Martin‐Jimenez, Cristina; De Veylder, Lieven; Cazareth, Julie; Engler, Gilbert; Grossi‐de‐Sa, Maria Fatima; de Almeida Engler, Janice
Abstract: Cell cycle control in galls provoked by root‐knot nematodes involves the activity of inhibitor genes like the Arabidopsis ICK/KRP members. Ectopic KRP1, KRP2 and KRP4 expression resulted in decreased gall size by inhibiting mitotic activity, whereas KRP6 induces mitosis in galls. Herein, we investigate the role of KRP3, KRP5 and KRP7 during gall development and compared their role with previously studied members of this class of cell cycle inhibitors. Overexpression of KRP3 and KRP7 culminated in undersized giant cells, with KRP3 OE galls presenting peculiar elongated giant cells. Nuclei in KRP3 OE and KRP5 OE lines presented a convoluted and apparently connected phenotype. This appearance may be associated with the punctuated protein nuclear localization driven by specific common motifs. As well, ectopic expression of KRP3 OE and KRP5 OE affected nematode development and offspring. Decreased mitotic activity in galls of KRP3 OE and KRP7 OE lines led to a reduced gall size which presented distinct shapes – from more elongated like in the KRP3 OE line to small rounded like in the KRP7 OE line. Results presented strongly support the idea that induced expression of cell cycle inhibitors such as KRP3 and KRP7 in galls can be envisaged as a conceivable strategy for nematode feeding site control in crop species attacked by phytopathogenic nematodes. Abstract : Plant cell cycle inhibitor genes control root‐knot nematode‐induced gall development. Ectopic expression of KRP3, KRP5 and KRP7 members reduces feeding cell size and interferes with giant cell nuclear morphology affecting nematode reproduction. Induced expression of these cell cycle inhibitors in galls can be envisaged as a novel strategy to control phytopathogenic nematodes in crop species.